Reconstruction of Police Legal Policy in Preventing Human Trafficking Crimes through Digital Platforms as a Transnational Crime in Indonesia - M. Reza Pranata; Sutrisno Sutrisno; Kif Aminanto (Journal Customary Law, 2026)
Human trafficking through digital platforms has evolved into a modern transnational crime that utilizes social media, instant messaging applications, online job platforms, and digital technology to recruit and exploit victims across borders. This study aims to analyze police legal policies in preventing digital platform-based human trafficking crimes in Indonesia, identify regulatory weaknesses and empirical obstacles faced by the Indonesian National Police, and formulate a reconstruction of cyber-policing-based legal policies in preventing human trafficking as a transnational crime. This study employs a normative juridical method compared a legislative and a conceptual approaches through an analysis of various national regulations and international legal instruments related to human trafficking and digital law enforcement. The results show that applicable legal policies are not yet adaptive to the development of digital technology-based human trafficking because they are still oriented towards a repressive approach and do not specifically regulate digital trafficking, platform liability, cyber surveillance, and preventive cyber policing. In addition, the Indonesian National Police face structural, substantial, and technological obstacles such as limited digital forensics, the use of anonymous accounts and foreign servers, weak inter-agency coordination, and a suboptimal early detection system for human trafficking in cyberspace. Therefore, a reconstruction of police legal policy is needed through regulatory reformulation, strengthening cyber policing, establishing an integrated early warning system, utilizing artificial intelligence and big data, and strengthening international cooperation to create a more effective, adaptive, and human rights-oriented digital-based human trafficking prevention system in Indonesia.